The ubiquitous subunit of erythroid transcription factor NF-E2 is a small basic-leucine zipper protein related to the v-maf oncogene. - Andrews, N C (1993)
Erythroid transcription factor NF-E2 is a tissue-restricted heterodimeric protein which recognizes an extended AP-1 motif [(T/C)TGCTGA(C/G)TCA(T/C)] found in the upstream locus control regions of the alpha- and beta-globin gene clusters. A cDNA clone encoding a cell-type-specific subunit of NF-E2, designated p45 NF-E2, has previously been characterized and shown to encode a basic-leucine zipper DNA-binding protein. Here we describe protein purification and cloning of cDNA that encodes the second basic-leucine zipper subunit of the native NF-E2 heterodimer. This polypeptide, designated p18, is widely expressed. It displays extensive homology to the v-maf oncogene product and a human retinal-specific protein, NRL. Unusual features in the basic region shared by v-Maf, NRL, and p18 place them in a distinct subfamily of AP-1-like proteins.